High-Temperature Materials Systems: Emerging Applications, Materials, and Science Gaps: Proceedings of a Workshop-in Brief - Anne Johnson (The National Academies Press, 2023)
The U.S. Department of Defense faces a complex array of challenges in its efforts to retain a position of technological dominance and to protect national security. Several aspects of materials and manufacturing, especially the ability of materials to operate with predictable behaviors in high-temperature environments, pose particular challenges. To illuminate issues surrounding novel high-temperature materials discovery, development, manufacturing, and application, the National Academies of Sciences, Engineering, and Medicine hosted a workshop titled High-Temperature Materials Systems: Emerging Applications, Materials, and Science Gaps on May 10-11, 2022. This publication summarizes the presentations and discussion of the workshop.

The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
In the face of climate change, technological innovation, and global strategic competition, the U.S. Coast Guard will need to respond to many developments in the maritime domain over the next decade. The Coast Guard likely has sufficient statutory authority to respond to most of these developments, but some developments may call for new or clarified statutory authority as well as coordination with international bodies. Current statutory manning requirements, for example, will limit the Coast Guard2019s ability to authorize the regulated use of uncrewed vessels with autonomous systems. New authority may also be needed to establish spaceflight-related safety zones applicable to foreign-flagged vessels within 200 nautical miles of the U.S. coastlines.These are among the findings in TRB Special Report 346: The Coast Guard2019s Next Decade: An Assessment of Emerging Challenges and Statutory Needs from the Transportation Research Board of the National Academy of Sciences, Engineering, and Medicine.The report emphasizes that in addition statutory authority, the Coast Guard will need key organizational and operational capabilities, including a well-trained workforce, to respond to future challenges. A short video charts the Coast Guard's next decade.

Building Resilience in the Face of Emerging Threats to Child and Youth Well-Being: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
In the face of growing threats to child and youth well-being - whether it be the COVID-19 pandemic, climate change, systemic racism, or new crises that have yet to arise - it is imperative that youth well-being be promoted through the development of strong resilience skills. To explore strategies for building youth resilience, the National Academies of Sciences, Engineering, and Medicine Forum for Childrens Well-Being held a 3-day workshop in October 2022. The workshop included presentations from experts, as well as moderated conversations between the presenters and youth discussants. This Proceedings of a Workshop-in Brief provides a high-level summary of the topics addressed in the workshop.

Emerging Stronger from COVID-19: Priorities for Health System Transformation - National Academy of Medicine (The National Academies Press, 2023)
In mid-2022, the United States has lost more than 1 million people to the COVID-19 pandemic. We have been real-time witnesses to scores of heroic responses to the disease, death, inequity, and economic strife unleashed by the virus, but have also experienced the consequences of poor pandemic preparedness and long-standing structural failures in our health system. For decades, the U.S. health system has fallen far short of its potential to support and improve individual and population health. The COVID-19 pandemic has presented death and devastation2014but also an unprecedented opportunity to truly transform U.S. health, health care, and health delivery. To capitalize on this opportunity, the National Academy of Medicine gathered field leaders from across all of the major health system sectors to assess how each sector has responded to the pandemic and the opportunities that exist for health system transformation. The opportunity is now to capitalize on the hard-won lessons of COVID-19 and build a health care system that centers patients, families, and communities; cares for clinicians; supports care systems, public health, and biomedical research to perform at the best of their abilities; applies innovations from digital health and quality, safety, and standards organizations; and encourages health care payers and health product manufacturers and innovators to produce products that benefit all.

Fundamental Research in High Energy Density Science - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
High energy density (HED) science has critical applications for society from fusion energy to sustaining the US nuclear deterrent, while also contributing to broader scientific questions such as understanding planets and their origins. The next decade of HED science will be instrumental to growing our understanding and in the development of new technologies and processes. Fundamental Research in High Energy Density Science identifies key challenges and science questions for the field for the coming decade and proposes ways to address them.

Transforming EPA Science to Meet Today's and Tomorrow's Challenges - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Since its establishment in 1970, the mission of the Environmental Protection Agency is to protect human health and the environment. EPA develops regulations, ensures compliance, and issues policies, in coordination with state, tribal, and local governments. To accomplish its mission, EPA should be equipped to produce and access the highest quality and most advanced science. The Office of Research and Development (ORD) provides the scientific bases for regulatory and public health policies that have broad impacts on the nation2019s natural resources and quality of human life, and that yield economic benefits and incur compliance costs for the regulated community. In addition, ORD develops the agency core research capabilities, providing tools and methods for meeting current and anticipating future environmental challenges, such as the risks to health and the environment posed by climate change. Because challenges associated with environmental protection today are complex and affected by many interacting factors, the report points to the need for a substantially broader and better integrated approach to environmental protection. This report calls for EPA ORD to pursue all of its scientific aims in a new framework2014to apply systems thinking to a One Environment 2212 One Health approach in all aspects of ORD work. To accomplish this, the report provides actionable recommendations on how ORD might consider incorporating emerging science and systems thinking into the agency research planning, so that ORD can become an increasingly impactful organization. The report identifies a number of high-priority recommendations for ORD to pursue in taking advantage of a broad range of advanced tools, in concert with collaborators in other federal agencies and the broader scientific community. Given the resource constraints, the report recognizes that ORD will have to make decisions about priorities for implementing its recommendations, and that ORD leadership is in the best position to set those priorities as implementation begins. The report concluded by stating that shifting to a systems-thinking approach will require renewed support from science leadership, enhanced strategic planning, investment in new and broader expertise and tools, and a reimagined and inclusive commitment to communication and collaboration.

Review of the SBIR and STTR Programs at the National Science Foundation - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The National Science Foundation (NSF) asked the National Academies of Sciences, Engineering, and Medicine to conduct a quadrennial review of the NSF Small Business Innovation Research (SBIR) and Small Business Technology Transfer (STTR) programs, in accordance with a legislative mandate. Drawing on published research plus existing data, Review of the SBIR and STTR Programs at the National Science Foundation analyzes the effectiveness of NSF award selection process and postaward assistance; the effectiveness of the STTR program in stimulating new collaborations; the economic and noneconomic impacts of the programs; effectiveness of the programs in stimulating technological innovation and supporting small, new firms across the technological spectrum; and the role of the programs in providing early capital to firms without other significant sources of support.

Origins, Worlds, and Life: Planetary Science and Astrobiology in the Next Decade - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The next decade of planetary science and astrobiology holds tremendous promise. This booklet highlights key science questions, identifies priority missions, and presents a research strategy that includes both planetary defense and human exploration.

Nonhuman Primate Models in Biomedical Research: State of the Science and Future Needs - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Nonhuman primates represent a small fraction of animals used in biomedical research, but they remain important research models due to their similarities to humans with respect to genetic makeup, anatomy, physiology, and behavior. Limitations in the availability of nonhuman primates have been exacerbated by the COVID-19 pandemic and recent restrictions on their exportation and transportation, impacting National Institutes of Health (NIH)-funded research necessary for both public health and national security. Additionally, there is continued interest in understanding whether and how nonanimal models can be used to answer scientific questions for which nonhuman primates are currently used. At the direction of the U.S. Congress, NIH asked the National Academies of Sciences, Engineering, and Medicine to convene an expert committee to conduct a landscape analysis of current and future use of nonhuman primates in NIH-supported biomedical research, as well as opportunities for new approach methodologies to complement or reduce reliance on nonhuman primate models. This report provides the committee findings and conclusions.

Advancing Chemistry and Quantum Information Science: An Assessment of Research Opportunities at the Interface of Chemistry and Quantum Information Science in the United States - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The field of quantum information science (QIS) has witnessed a dramatic rise in scientific research activities in the 21st century as excitement has grown about its potential to revolutionize communications and computing, strengthen encryption, and enhance quantum sensing, among other applications. While, historically, QIS research has been dominated by the field of physics and computer engineering, this report explores how chemistry - in particular the use of molecular qubits - could advance QIS. In turn, researchers are also examining how QIS could be used to solve problems in chemistry, for example, to facilitate new drug and material designs, health and environmental monitoring tools, and more sustainable energy production. Recognizing that QIS could be a disruptive technology with the potential to create groundbreaking products and new industries, Advancing Chemistry and Quantum Information Science calls for U.S. leadership to build a robust enterprise to facilitate and support research at the intersection of chemistry and QIS. This report identifies three key research areas: design and synthesis of molecular qubit systems, measurement and control of molecular quantum systems, and experimental and computational approaches for scaling qubit design and function. Advancing Chemistry and Quantum Information Science recommends that the Department of Energy, National Science Foundation, and other funding agencies should support multidisciplinary and collaborative research in QIS, the development of new instrumentation, and facilities, centralized and open-access databases, and efforts to create a more diverse and inclusive chemical workforce.

Assessment of Commercial Space Platforms for Earth Science Instruments: Report Series—Committee on Earth Science and Applications from Space - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Space-based Earth observations enable global observations of the land surface, biosphere, solid Earth, atmosphere, cryosphere, and oceans. Earth observations from space, combined with data acquired from in situ and ground-based instruments, help scientists understand the components of the Earth system and their interactions and enable wide-ranging applications, including forecasts of weather and air quality, projections of future climate, management of natural resources, ecological forecasting, disaster management, drought and wildfire prediction, and the mapping and prediction of vector borne\/animal diseases. At the request of NASA Earth Science Division, this report assesses the potential use of a proposed multi-user, robot-tended, uncrewed commercial space platform as a potential host for a large number of Earth remote sensing instruments. Assessment of Commercial Space Platforms for Earth Science Instruments evaluates the utility and practicality of a platform in a Sun-synchronous orbit, capable of hosting 20 or more instruments.

Foundations of Data Science for Students in Grades K-12: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
On September 13 and 14, 2022, the Board on Science Education at the National Academies of Sciences, Engineering, and Medicine held a workshop entitled Foundations of Data Science for Students in Grades K201312. Speakers and participants explored the rapidly growing field of K-12 data science education, by surveying the current landscape, surfacing what is known, and identifying what is needed to support student learning, develop curriculum and tools, and prepare educators. To support these conversations, four papers were commissioned and discussed during the workshop. This publication summarizes the presentations and discussion of the workshop.

Openness, International Engagement, and the Federally Funded Science and Technology Research Enterprise: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
On November 14 and 15, 2022, the National Academies of Sciences, Engineering, and Medicine convened a two-day workshop under the auspices of the National Science, Technology, and Security Roundtable to assess the state of the U.S. research enterprise in a time of increasing global competition. The workshop also featured discussion of the challenges confronting researchers as they seek to ensure the vitality of research and innovation in America, foster increased international scientific research cooperation, and simultaneously counter illicit foreign interference that threatens national security interests. This publication summarizes the presentation and discussion of the workshop.

Barriers, Challenges, and Supports for Family Caregivers in Science, Engineering, and Medicine: Proceedings of Two Symposia - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Before the COVID-19 pandemic, research demonstrated a significant impact of family caregiving responsibilities on the careers of professionals who work in science, technology, engineering, mathematics, and medicine (STEMM) - especially women. The COVID-19 pandemic increased public recognition of the challenges experienced by caregivers in STEMM fields and created a sense of urgency among many stakeholders. As part of the information-gathering stage of a forthcoming consensus study to address the barriers faced by caregivers, of all genders, in STEMM fields, the Committee on Policies and Practices for Supporting Family Caregivers Working in Science, Engineering, and Medicine organized two national symposia on February 27 and March 27, 2023. Scholars and leaders from a range of sectors convened to identify evidence-based interventions that can support the recruitment, retention, and advancement of caregivers in science, engineering, and medical fields. This publication summarizes the presentations and discussion of the symposia.

Exploring the Use and Application of Implementation Science in Health Professions Education: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Implementation science bridges the gap between research and medical practice, investigating aspects of practice and pedagogy that make the strategies successful for future use. By introducing and training leaders, faculty, and health workforce researchers in implementation science, health professions education institutions can build capacity for evidence-based practices. The National Academies Global Forum on Innovation in Health Professional Education held a workshop series to introduce the concept of implementation science to health professional educators to consider its potential use in the classroom. Speakers provided a foundation for discussion of the role of implementation science in health professions education and provided methods for educators interested in applying these recommendations to scale. This Proceedings of a Workshop highlights the presentations and discussions that occurred at the workshop.

Reducing Racial Inequality in Crime and Justice: Science, Practice, and Policy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The history of the U.S. criminal justice system is marked by racial inequality and sustained by present day policy. Large racial and ethnic disparities exist across the several stages of criminal legal processing, including in arrests, pre-trial detention, and sentencing and incarceration, among others, with Black, Latino, and Native Americans experiencing worse outcomes. The historical legacy of racial exclusion and structural inequalities form the social context for racial inequalities in crime and criminal justice. Racial inequality can drive disparities in crime, victimization, and system involvement. Reducing Racial Inequality in Crime and Justice: Science, Practice, and Policy synthesizes the evidence on community-based solutions, noncriminal policy interventions, and criminal justice reforms, charting a path toward the reduction of racial inequalities by minimizing harm in ways that also improve community safety. Reversing the effects of structural racism and severing the close connections between racial inequality, criminal harms such as violence, and criminal justice involvement will involve fostering local innovation and evaluation, and coordinating local initiatives with state and federal leadership. This report also highlights the challenge of creating an accurate, national picture of racial inequality in crime and justice: there is a lack of consistent, reliable data, as well as data transparency and accountability. While the available data points toward trends that Black, Latino, and Native American individuals are overrepresented in the criminal justice system and given more severe punishments compared to White individuals, opportunities for improving research should be explored to better inform decision-making.

Opportunities and Challenges for Digital Twins in Atmospheric and Climate Sciences: Proceedings of a Workshop—in Brief - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The digital twin is an emerging technology that builds on the convergence of computer science, mathematics, engineering, and the life sciences. Digital twins have the potential to revolutionize atmospheric and climate sciences in particular, as they could be used, for example, to create global-scale interactive models of Earth to predict future weather and climate conditions over longer timescales. On February 1-2, 2023, the National Academies of Sciences, Engineering, and Medicine hosted a public, virtual workshop to discuss characterizations of digital twins within the context of atmospheric, climate, and sustainability sciences and to identify methods for their development and use. Workshop panelists presented varied definitions and taxonomies of digital twins and highlighted key challenges as well as opportunities to translate promising practices to other fields. The second in a three-part series, this evidence-gathering workshop will inform a National Academies consensus study on research gaps and future directions to advance the mathematical, statistical, and computational foundations of digital twins in applications across science, medicine, engineering, and society.

Rise and Thrive with Science: Teaching PK-5 Science and Engineering - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Research shows that that children learn science and engineering subjects best by engaging from an early age in the kinds of practices used by real scientists and engineers. By doing science and engineering, children not only develop and refine their understanding of the core ideas and crosscutting concepts of these disciplines, but can also be empowered to use their growing understanding to make sense of questions and problems relevant to them. This approach can make learning more meaningful, equitable, and lasting. Using cases and shorter examples, Rise and Thrive with Science shows what high-quality teaching and learning in science and engineering can look like for preschool and elementary school children. Through analyses of these examples and summaries of research findings, the guide points out the key elements of a coherent, research-grounded approach to teaching and learning in science and engineering. This guide also discusses the kinds of support that educators need to implement effective and equitable instruction for all children. This book will provide inspiration for practitioners at the preschool and elementary levels to try new strategies for science and engineering education, whatever their level of experience. Rise and Thrive with Science will be an essential guide for teachers as they organize instruction to enable young children to carry out their own science investigations and engineering design projects, determine the kinds of instruction that lead to meaningful learning, and try to engage every one of their students.

Reflections on the National Science Foundation's Understanding the Rules of Life Program: Proceedings of a Workshop Series - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
In 2016, the National Science Foundation (NSF) established a five-year program on Understanding the Rules of Life (URoL) to identify generalizable rules that govern biological systems at micro and macro levels. At the request of NSF, the National Academies of Sciences, Engineering, and Medicine convened a series of workshops to explore the achievements of the URoL program. Presenters and participants discussed integration of multi-disciplinary, systems-level approaches, broader implications for studying highly complex systems, future scientific questions and future societal needs, and the production of generalizable rules that apply to different fields and scales. This publication summarizes the presentation and discussion of the workshop.

Psychological Factors That Contribute to the Dearth of Black Students in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Efforts over the last several decades to increase the participation and leadership of Black men and women in the scientific and medical workforce have had limited results. Despite many individual successes, the number of Black professionals in science, engineering, and medicine (SEM) fields has not reached a level that corresponds with African American representation in the country at large. Structural racism affects progress at all stages along the pathway - from young children through graduate and medical students through faculty and clinicians at all levels. Beyond entry into educational programs or recruitment into workplaces seeking to diversify, challenges persist to achieve equity and inclusion for Black males and females. Moreover, psychological barriers confound the engagement of Black men and women in SEM fields. To explore these issues and suggest solutions, the National Academies of Sciences, Engineering, and Medicine launched the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine. Over the past 2 years, the Roundtable has convened workshops on K-12 education, the impact of COVID-19, financial burdens to pursuing SEM careers, and other topics. Sessions during each of these workshops identified psychological factors related to those specific topics. To have a more targeted discussion, the Roundtable convened a virtual workshop on September 14-15, 2021. As summarized in this proceedings, panelists and participants identified policies and practices that perpetuate these factors and explored solutions toward achieving and maintaining wellness, especially among students and young professionals.